Waterlogging, Salinity and Combined Stress a Major Problem in Pigeonpea (Cajanus cajans L. Mill sp.) - Duhan, Savita; Sheokand, Sunita; Kumari, Anita (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was conducted in Department of Botany and Plant Physiology, CCS Haryana Agricultural University, Hisar during 2014−15 and 2015−16. Waterlogging and salinity are most severe stress all around the world. When water and salt is present in excess amount than its optimum requirement it refers to waterlogging and salinity respectively. Waterlogging when combined with salinity exaberate the effect of salinity. Four pigeonpea genotypes (ICPH-2431, PARAS, UPAS-120, H09-33) were raised in polythene bags filled with half kg soil+FYM manure mixture and Carbohydrate metabolism and aerenchyma formation under twelve days waterlogging, salinity and combined stress was studied in roots of 20 and 40 day old pigeonpea plants 1, 4 and 8 days after removal from treatment under pot house conditions. Decline in total and nonreducing sugar content and a significant increase in reducing sugar content, sucrose synthase activity and alcohol dehydrogenase activity was observed with waterlogging and salinity stress. No survival was observed under combined waterlogging and salinity treatment in any genotypes. Waterlogging was found more deleterious compared to alone salinity treatment. Aerenchyma formation was observed only under waterlogging treatment. Both the stresses are found more deleterious when given at later stages of growth. ICPH performed best among all the genotypes followed by PARAS, HO9-33 and UPAS-120 in terms of total sugar, nonreducing sugar, reducing sugar, sucrose synthase activity, alcohol dehydrogenase activity and aerenchyma formation.